Haplotype-based mapping and pharmacogenetics - Goldstein, David (Henry Stewart Talks, 2004)
Pharmacogenetics: a simpler complex trait?, Mapping strategies: map-based and sequence-based, Tagging SNPs: definition and assessment, Case study: tagging in 56 drug transport and metabolism genes, tSNP efficiency: influence of sample size, SNP frequency and SNP density, Case study: ABCB1 and anti-epileptic drug resistance, Associated interval
Archived at 2021/02/25